(untitled) (Scientific journal of the Fergana State University, 2024)
The article delves into the comic artistry of poet Erkin Vahidov, focusing particularly on his satirical and humorous poems. These works are analyzed within the context of interpreting contemporary issues, examining the author’s "I" and the creative’s artistic and aesthetic mindset. In the "Wise Village Anecdotes" series, the essence of comedy and sarcasm, the nature of lyrical experience, and the poet’s talent for crafting comic imagery are brought to light through an analysis of the character Matmusa.